Penerapan Algoritma Regresi Linear Sederhana untuk Prediksi Penjualan Produk pada PT. Bintang Graha Makmur - Rifky, Muhammad; Samosir, Ridha Sefina (UNIVERSITAS KALBIS, 2025)
PT Bintang Graha Makmur in Jakarta is a company that has been operating since 2010 in the field of food and beverages, especially alcoholic beverages. Until now, PT Bintang Graha Makmur has distributed alcoholic beverage products to various restaurants, hotels and bars. The problem that often occurs at this time is the difficulty in determining the right stock of goods, resulting in delays in shipping goods. This prediction is done to estimate future sales to make decisions in stocking goods so that they are able to adjust to the amount of demand for goods. The sales prediction method used is Simple Linear Regression and then the prototyping system development method which is applied in the form of a website. The results of this study are to produce an average value of MAPE from each prediction result of each product and help to process records on sales of goods, stock items and customers.